2015
DOI: 10.1177/1947603515571002
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Mesenchymal Stem Cell (MSC)–Based Cartilage Repair Using Scaffold-Free Tissue Engineered Constructs Generated with Synovial Mesenchymal Stem Cells

Abstract: Because of its limited healing capacity, treatments for articular cartilage injuries are still challenging. Since the first report by Brittberg, autologous chondrocyte implantation has been extensively studied. Recently, as an alternative for chondrocyte-based therapy, mesenchymal stem cell-based therapy has received considerable research attention because of the relative ease in handling for tissue harvest, and subsequent cell expansion and differentiation. This review summarizes latest development of stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 89 publications
0
40
0
1
Order By: Relevance
“…ACI is a two-step procedure that consists of healthy cartilage harvesting through arthroscopy followed by the expanded cell culture and, in a second step, cartilage defect filling (13)(14)(15). In spite of second and third ACI generations' versatility, those techniques use healthy cartilage tissue, "in vitro" related chondrocytes dedifferentiation and still fails to fully reproduce the hyaline characteristics of the original articular cartilage (6,13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACI is a two-step procedure that consists of healthy cartilage harvesting through arthroscopy followed by the expanded cell culture and, in a second step, cartilage defect filling (13)(14)(15). In spite of second and third ACI generations' versatility, those techniques use healthy cartilage tissue, "in vitro" related chondrocytes dedifferentiation and still fails to fully reproduce the hyaline characteristics of the original articular cartilage (6,13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, mesenchymal stem cell-based therapy has received considerable attention, because of the feasibility of handling the tissue harvest and ex vivo cell expansion and differentiation (12,13). Moreover, these cells present minor immunological rejection due to the low surface expression of major histocompatibility complex (MHC) antigens, efficient engraftment and long-term coexistence in the host, which turns them an attractive therapeutic option (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…SMSCs are an emerging cell source for regenerative medicine applications, including for bone 29,30 and cartilage [24][25][26][27] applications. The long-term goal of this work was to identify scaffold-based biochemical cues capable of guiding zonallytailored SMSC differentiation for OCD repair.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In addition, although bone marrow MSC responses to a range of scaffold-based biochemical stimuli have been systematically examined, SMSC responses to 3D scaffold formulations are just beginning to be understood and characterized. For example, a majority of the work with SMSCs has focused on chondrogenic applications with scaffold-free approaches 24,25 or using a variety of different scaffolds, including collagen 26 and gelatin-dextran. 27 However, studies which allow comparison of SMSC differentiation in response to defined scaffold-based biochemical signals are limited, 28 as are reports of scaffold-based SMSC osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Such autologous synovial MSCs were applied to cartilage injury 29. Currently, only one clinical study repairing chondral defect using scaffold-free three-dimensional tissue engineered construct, derived from human synovial MSCs, was completed in March 2015; but, the outcomes of the study were not reported 30,31. This may be considered to be evident that these naturally occurring MSCs may play an important role in meniscal healing and regeneration.…”
Section: Introductionmentioning
confidence: 99%